Performa Produksi Burung Puyuh (Coturnix-Coturnix Japonica) Fase Layer yang Diberi Ransum Mengandung Dedak Padi Fermentasi - Maulana, Abdul Jabbar; Napirah, Astriana; Has, Hamdan (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
A major challenge in the quail farming industry is the reliance on commercial feed, most of which is imported. This study aims to evaluate the production performance of layer-phase quail (coturnix-coturnix japonica) fed a ration containing fermented rice bran. This research was carried out in October-November 2021. The research design used was a completely randomized design (CRD) with 4 (four) treatments and each treatment was repeated 5 (five) times where each replication consisted of 5 (female) quails. Parameters observed were feed consumption, egg production, egg weight, and feed conversion. Based on the results of the study, it was concluded that the use of rice bran at the level of 20% and 25% both fermented and unfermented had a significant effect on feed conversion and quail egg weight but had no significant effect on feed consumption and egg production. Feeding containing 20% fermented rice bran showed the highest egg weight (12.84 g) and the lowest feed conversion value (4.18). It was concluded that the use of rice bran at the level of 20% and 25%, both fermented and unfermented, had a significant effect on feed conversion and egg weight of quails but no significant effect on feed consumption and egg production.